High-Temperature Creep Resistance of FeAlOY ODS Ferritic Alloy - Dymáček, Petr; Jarý, Milan; Bártková, Denisa; Luptáková, Natália; Gamanov, Štěpán; Bořil, Petr; Georgiev, Vjačeslav; Svoboda, Jiří (MDPI, 2024)
A significant effort in optimizing the chemical composition and powder metallurgical processing led to preparing new-generation ferritic coarse-grained ODS alloys with a high nano-oxide content. The optimization was aimed at high-temperature creep and oxidation resistance at temperatures in the range of 1100-1300 degrees C. An FeAlOY alloy, with the chemical composition Fe-10Al-4Cr-4Y2O3 (wt. %), seems as the most promising one. The consolidation of the alloy is preferably conducted by hot rolling in several steps, followed by static recrystallization for 1 h at 1200 degrees C, which provides a stable coarse-grain microstructure with homogeneous dispersion of nano-oxides. This represents the most cost-effective way of production. Another method of consolidation tested was hot rotary swaging, which also gave promising results. The compression creep testing of the alloy at 1100, 1200, and 1300 degrees C shows excellent creep performance, which is confirmed by the tensile creep tests at 1100 degrees C as well. The potential in such a temperature range is the target for possible applications of the FeAlOY for the pull rods of high-temperature testing machines, gas turbine blades, or furnace fan vanes. The key effort now focuses on expanding the production from laboratory samples to larger industrial pieces.

A significant effort in optimizing the chemical composition and powder metallurgical processing led to preparing new-generation ferritic coarse-grained ODS alloys with a high nano-oxide content. The optimization was aimed at high-temperature creep and oxidation resistance at temperatures in the range of 1100-1300 degrees C. An FeAlOY alloy, with the chemical composition Fe-10Al-4Cr-4Y2O3 (wt. %), seems as the most promising one. The consolidation of the alloy is preferably conducted by hot rolling in several steps, followed by static recrystallization for 1 h at 1200 degrees C, which provides a stable coarse-grain microstructure with homogeneous dispersion of nano-oxides. This represents the most cost-effective way of production. Another method of consolidation tested was hot rotary swaging, which also gave promising results. The compression creep testing of the alloy at 1100, 1200, and 1300 degrees C shows excellent creep performance, which is confirmed by the tensile creep tests at 1100 degrees C as well. The potential in such a temperature range is the target for possible applications of the FeAlOY for the pull rods of high-temperature testing machines, gas turbine blades, or furnace fan vanes. The key effort now focuses on expanding the production from laboratory samples to larger industrial pieces.
High-Temperature Creep Resistance of FeAlOY ODS Ferritic Alloy
Keywords: oxide-dispersion-strengthened (ODS) alloy; mechanical alloying; high-temperature; creep; threshold stress; oxide-dispersion-strengthened (ODS) alloy; mechanical alloying; high-temperature; creep; threshold stress